Mechanics of freely‐suspended ultrathin layered materials. Issue 1 (9th October 2014) - Castellanos‐Gomez, Andres; Singh, Vibhor; van der Zant, Herre S. J.; Steele, Gary A.; Harris, Jack; Rabl, Peter; Schliesser, Albert
<x xml:space="preserve">Abstract</x> In this manuscript the experimental methods recently developed to study the mechanical properties of 2D materials are reviewed. A thorough comparison between the mechanical properties of various 2D materials with very different properties (conductors, semiconductors and insulators) is presented. This article also discusses the advances towards applying 2D materials in nanomechanical devices, comparing the different results available in the literature for a wide variety of 2D materials studied to date. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>